GAMBARAN MOTIVASI KEPALA KELUARGA DALAM PEMBERANTASAN NYAMUK AEDES AEGYPTI DI DUSUN JEMBRUNG 2 BULUSARI GEMPOL KABUPATEN PASURUAN - Dwi, Binarti; Eki Asfrianti, Riska (JURNAL KEPERAWATAN SEHAT, 2014)
MosquitoAedes aegyptiis a major causeof Dengue Hemorrhagic Fever(DHF) ischaracterized bysudden onset of fever, bleedinginthe skinor other body parts, appearshockorshock, anddeath. So the need forhighly motivatedand spreadall over so that people aremoved tobe more careabout thehealth of the real participation of people forDHF.This researchaims to describe themotivation ofthe patriachinthe mosquitoAedesaegyptieradicationinthe hamlet Jembrung2BulusariGempolPasuruan district. The designof this studyusing themethodDiskriptif. The samplingmethodusedisNon-ProbabilityTypepurposivesampling. Samples takenby 30 respondentsareheads of householdsin the hamlet2BulusariGempolJembrungPasuruanregency. The research datawas takenusing aquestionnairesheet. The results showedthat thechiefmotivation ofthe familyof 30respondents,3respondentspick thehighmotivation(10%) of 17respondentshavemoderatemotivation(56.7%) andas many as10respondentshavelessmotivation(33.3%). Viewingresearch resultsistheneed forspecial attentionto thehead ofthe familyin the eradication ofAedes aegypti mosquitothathasmotivatedso as to reducethe incidence ofdengue diseasewhichhas led toa variety ofsocial unresteach year.